Angiographic Finding in Acute Coronary Syndrome in Female Patient’s Diabetic vs Non-Diabetic - Cheragh Hussain, Muhammad Hussain Afridi, Akbar Shah, Shaista Kawanl, Nizamuddin, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: From January 2018 to July 2018, a study was conducted at Hayatabad Medical Complex's Department of Cardiology to analyze the angiographic results of female patients admitted for acute coronary syndrome (ACS). The study group consisted of 75 female patients with ACS; thirty patients were diabetic, while the remaining forty-five were non-diabetic. Results from angiography revealed that single vessel disease (36.67%) was the most common finding in non-diabetic patients, followed by two vessel disease (31.11%). The study found that disease severity in diabetic patients varied more, with the majority (43.33%) having two vessel disease. Single vessel disease (33.33%) and three vessel disease (23.33%) were also frequently observed. Conversely, non-diabetic patients displayed more normal coronaries (44.44%) while diabetic patients tended to have more diseased vessels (66.67%). Ultimately, the study determined that female diabetics with ACS exhibit a wider range of complex diseases compared to their non-diabetic counterparts. Objectives: From January 2018 to July 2018, Department of Cardiology at Hayatabad Medical Complex in Peshawar received admissions for acute coronary syndrome (ACS) in both diabetic and non-diabetic female patients. Our present study aims to compare the findings of their angiograms. Methodology: The present study had 75 female patients admitted to Hayatabad Medical Complex's Cardiology Department between January and July 2018 for ACS. Medical records were reviewed for age, medical history, and angiography findings. A comparison of non-diabetic and diabetic patients showed 45 and 30 patients, respectively. The severity of the ACS was determined by the number of vessel involvement and coronary artery status in the angiography report. Results: Single vessel disease was identified as the most common finding in 36.67% of non-diabetic patients, while two vessel disease was noted in 31.11%. However, in diabetic patients, the most frequent discovery was two vessel disease with 43.33%, followed by single vessel disease in 33.33% and three vessel disease in 23.33%. In terms of coronary artery status, more non-diabetic patients had normal coronaries (44.44%) in contrast to diabetic patients who showed more diseased vessels with a percentage of 66.67%. Conclusion: The study revealed a greater range and complexity of illness severity among female ACS patients with diabetes than those without. This indicates that those with diabetes are more susceptible to severe ACS forms, underscoring the importance of their careful monitoring to minimize the chances of cardiovascular complications. Keywords: ACS, Angiography, Diabetic, Non-Diabetic, Coronary Artery.